2021
DOI: 10.1155/2021/5626228
|View full text |Cite|
|
Sign up to set email alerts
|

Mathematical Analysis of Application of a Three-Dimensional Printing Fixator in the Fracture of Multiple Ribs

Abstract: Data were obtained from 66 clinical patients. The patients were divided into a non-3D printing group (control group) and a 3D printing group (intervention group) in a 1 : 1 ratio, with 33 patients in each group. The information including gender, age, incision length, number of surgical roots, bleeding volume, operation time, and intraoperative blood transfusion was collected for SPSS analysis. The results showed the following: (1) The paired t-test was used to test the difference of experimental data. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%